Coarse graining of force fields for metal–organic frameworks. Issue 10 (6th January 2016) - Dürholt, Johannes P.; Galvelis, Raimondas; Schmid, Rochus
Abstract : We have adapted our genetic algorithm based optimization approach, originally developed to generate force field parameters from quantum mechanic reference data, to derive a first coarse grained force field for a MOF, taking the atomistic MOF-FF as a reference. Abstract : We have adapted our genetic algorithm based optimization approach, originally developed to generate force field parameters from quantum mechanic reference data, to derive a first coarse grained force field for a MOF, taking the atomistic MOF-FF as a reference. On the example of the copper paddle-wheel based HKUST-1, a maximally coarse grained model, using a single bead for each three and four coordinated vertex, was developed as a proof of concept. By adding non-bonded interactions with a modified Buckingham potential, the resulting MOF-FF-CGNB is able to predict local deformation energies of the building blocks as well as bulk properties like thetbo vs. pto energy difference or elastic constants in a semi-quantitative way. As expected, the negative thermal expansion of HKUST-1 is not reproduced by the maximally coarse grained model. At the expense of atomic resolution, substantially larger systems (up to tens of nanometers in size) can be simulated with respect to structural and mechanical properties, bridging the gap to the mesoscale. As an example the deformation of the [111] surface of HKUST-1 by a "tip" could be computed without artifacts from periodic images.